Promoting information and librarianship in Nigeria through research publications: the role of female academics (2011)
The study investigates the previous contributions of female academics in the field of information and librarianship for information development through their research publication efforts. The investigation is bared on the data generated through a set of questionnaire purposely designed to generate response on authorship of research paper, areas of interest, reasons for Publishing and contributions through organised Professional gatherings. It was confirmed that female academics in information and librarianship profession in Nigeria are active participant in national information development It was concluded that there is room for improvement especially in the area of research for Professional development. The new entrants are challenged to take the profession to the next level through research.